A review on glass welding by ultra-short laser pulses - Cvecek, Kristian; Dehmel, Sarah; Miyamoto, Isamu; Schmidt, Michael (International Journal of Extreme Manufacturing, 2019)
Glass welding by ultra-short pulsed (USP) lasers is a piece of technology that offers high strength joints with hermetic sealing. The joints are typically formed in glass that is transparent to the laser by exploiting nonlinear absorption effects that occur under extreme conditions. Though the temperature reached during the process is on the order of a few 1000 °C, the heat affected zone (HAZ) is confined to only tens of micrometers. It is this controlled confinement of the HAZ during the joining process that makes this technology so appealing to a multitude of applications because it allows the foregoing of a subsequent tempering step that is typically essential in other glass joining techniques, thus making it possible to effectively join highly heat sensitive components. In this work, we give an overview on the process, development and applications of glass welding by USP lasers.<br